2012
DOI: 10.1140/epje/i2012-12061-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of thin confined polymer films close to the glass transition in the linear regime of deformation: Theory and simulations

Abstract: Over the past twenty years experiments performed on thin polymer films deposited on substrates have shown that the glass transition temperature T(g) can either decrease or increase depending on the strength of the interactions. Over the same period, experiments have also demonstrated that the dynamics in liquids close to the glass transition temperature is strongly heterogeneous, on the scale of a few nanometers. A model for the dynamics of non-polar polymers, based on percolation of slow subunits, has been pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
95
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(107 citation statements)
references
References 90 publications
10
95
2
Order By: Relevance
“…This crudely leads to a film with some fraction of glassy segments that can effectively pin the polymer chains on the time scale of the measurements . This explanation is similar to the arguments from Dequidt et al where their model uses the broadening of T g on confinement to predict as much as an order of magnitude increase in the modulus between bulk T g and T g + 50 K in comparison to the bulk polymer . Recently, Priestley and coworkers elegantly demonstrated that there is a gradient in viscosity through polymer thin films when probed with non‐contact shear, which is consistent with the distribution of properties explanation of Mirigian and Schweizer.…”
Section: Flow Properties Of Rubbery Polymers Under Confinementsupporting
confidence: 76%
“…This crudely leads to a film with some fraction of glassy segments that can effectively pin the polymer chains on the time scale of the measurements . This explanation is similar to the arguments from Dequidt et al where their model uses the broadening of T g on confinement to predict as much as an order of magnitude increase in the modulus between bulk T g and T g + 50 K in comparison to the bulk polymer . Recently, Priestley and coworkers elegantly demonstrated that there is a gradient in viscosity through polymer thin films when probed with non‐contact shear, which is consistent with the distribution of properties explanation of Mirigian and Schweizer.…”
Section: Flow Properties Of Rubbery Polymers Under Confinementsupporting
confidence: 76%
“…52 Changes in the Young modulus upon confinement have also been reported in other studies. 52−56 Recently, Dequidt et al 57 made DPD simulations of the reinforcement of polymer films confined under strongly attractive substrates. They found thickness-dependent peaks in the plots of reinforcement vs temperature at temperatures above the bulk T g , which were attributed to the increased T g of the films due to the presence of the attractive surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the relation for T g (z), the thickness of the glassy layer z th at temperature T can be estimated by T g (z th ) = T , i.e., z th = βT g,b / T − T g,b . The divergence in T g (z) is purely formal, since the physics which lead to this relation [50,51] has a natural cutoff at short distance of about 2 nm. The corresponding increase in the glass transition temperature, about 100 K at 2 nm in their system, corresponds to the increase of T g measured in [7], either in mechanical experiments or by using NMR.…”
Section: Relaxation Of Glassy Bridgesmentioning
confidence: 99%
“…In particular, the value we chose for the parameter β = 0.8 nm, which sets the amplitude of the T g -shift in the vicinity of the fillers, has been considered in [18], and corresponds to that measured experimentally in [6,7]. The only parameter that is slightly adapted from the many-particle simulations in [18][19][20] to our two-particle model is the stress sensitivity K in (51). In [18], K is determined such that, when imposing an oscillatory strain with amplitude 0.1 and rate 0.1 s −1 , the stress-induced shift of the glass transition temperature is 100 K at the maximum strain, which would result in K = 1.2 · 10 −20 J K −1 .…”
Section: Simulation Setupmentioning
confidence: 99%
See 1 more Smart Citation